Implementation of Islamic Spiritual Charge for Hospital Patients Dr. Sardjito Yogyakarta: Review of Islamic Law - Binarsa Binarsa (Jurnal Indonesia Sosial Sains, 2024)
In order to cause a sense of calm and comfort in the hearts of patients, spiritual compensation activities are held. The spiritual field of Dr. Sardjito Hospital coordinates this activity. Spirituality is a religious institution at Dr. Sardjito Hospital, which handles spiritual compensation activities for patients and care for corpses. However, in the implementation, especially the care of the corpse, there has been an error or violation of shari'a or Islamic law in carrying out the care of the corpse, namely, the body of the daughter bathed by a man who is not her mahram without the cause of shari'a / Islamic law that allows.  The purpose of the research is to find out what mistakes and factors cause violations of Islamic law, to find out what solutions to avoid violations of shari'a or Islamic law, and to find out the implementation of spiritual compensation at Dr. Sardjito Hospital: Review of Islamic Law. The author uses field and library research methods to complete the abovementioned research objectives. Sampling techniques are Observation, Interview, and Questionnaire. The samples are the Director of RSUP, Dr. Sardjito Yogyakarta, the Clergy Coach, the Head of the Nursing Division, the Head of Forensic Medicine Installation, the Clergy Coordinator, the Clergy Officer, the Forensic Medicine Installation Officer and Patients treated, and the data analysis method is quantitative analysis. The results are a form of mistakes: officers and families do not know Islamic law, forced / emergency, motivation to make money, and factors: No cooperation between mortuary office workers and spirituality, No training in corpse care, No supervision from superiors. The solutions are Coaching and care for corpses, increased cooperation, and good supervision. Clear pro tabs and sanctions. The conclusion is the implementation of spiritual compensation to patients in the hospital. Dr. Sardjito: Review of Islamic Law is in accordance with the Shari'a.